Synthetic 1‐Deoxynojirimycin N‐Substituted Peptides Offer Prolonged Disruption to N‐Linked Glycan Processing. Issue 12 (28th October 2014) - Aguilar, Aimé López; Escribano, Jaime; Wentworth, Paul; Butters, Terry D.
Abstract A panel of 1‐deoxynojirimycin (DNJ) N‐linked peptides were synthesized. Their IC50 values were measured in vitro against α‐glucosidases I and II and were found to be in the micromolar range for both isozymes, and better than that of the iminosugar NB‐DNJ (miglustat, 3) against α‐glucosidase II. Cell‐based studies revealed that although the free iminosugar 3 is most effective at disrupting N‐linked glycan processing for short‐term incubations (one day), when the cell‐based studies were extended to three days, the DNJ N‐linked tetrapeptide KDEL, which is an endoplasmic reticulum (ER)‐retaining sequence, performed far better than 3. In low inhibitor washout studies, NB‐DNJ inhibition was decreased to zero after 24 h, but DNJ–KDEL retained 13 % activity. This method offers a general approach for targeting drugs to the ER and prolonging their activity. Moreover, it is modular, so as new iminosugars of increased potency are discovered, they can be added to this template for targeting.